Application of the ICA-NSF to determine the water quality of the Ozogoche, Pichahuiña and Pomacocho rivers-Sangay National Park-Ecuador - Coello, Julio (2013)
The objective of this work was to establish water quality using the Water Quality Index (ICA) of the National Sanitation Foundation of the United States (NSF) in the high Andean rivers Ozogoche, Pichahuiña and Pomacocho (3,100 to 3,950 masl) that form part of the Sangay National Park in Ecuador, to analyze in the future the change generated by environmental changes and anthropic activities. For the physical-chemical and microbiological analysis, 6 monitoring points were established in the Ozogoche River, 8 in the Pichahuiña River and 4 in the Pomacocho for one year (February 2011 to February 2012), covering the dry and rainy seasons. The average results of nine analyzed parameters were used to determine the ICA of each river, determining that the three micro-basins present good quality. There are parameters that show greater variation such as total solids, sulfates and conductivity, the maximum peaks of which were reached in the months of least precipitation (from February to May).